Valoração e variações semânticas: um estudo das reinstanciações de estágios discursivos de Things Fall Apart e Arrow of God - Cliver Gonçalves Dias (2018)
This study investigates the re-instantiation of APPRAISAL (MARTIN; WHITE, 2005) in translated fictional texts from English into Portuguese. The aim is to investigate semantic variations in discursive phases of different discursive stages of two translated fictional texts. With a different perspective of descriptive translation studies, this investigation reports onMunday (2010, 2012a), Rosa (2008, 2013), Blauth (2015) e Dias e Magalhães (2017). It draws on the APPRAISAL System and on Martins (1992) Genre perspective. It also adopts both the model of textual analysis of APPRAISAL in fictional texts by Macken-Horarik (2003) and themodel of contrastive analysis of interlingual translation by Souza (2010). These models enable a semantic-discursive analysis of translated fictional texts, a type of analysis not carried out in the descriptive translation studies mentioned here. The methodology consisted of two main phases. The first phase encompassed the selection of the translated texts and source texts. The data includes two translated texts in Portuguese O mundo se despedaça (2009) and A flecha de Deus (2011) , both translated by Vera Queiroz da Costa e Silva, and their source texts in English Things Fall Apart (1994[1958]) and Arrow of God (1989[1964]) , by the Nigerian writer Chinua Achebe. The second phase comprised three subphases of procedures. In the first subphase, the three main discursive stages of the narratives were identified, and a group of discursive phases was selected from each discursive stage of each narrative. For each group of phases of the source texts, the equivalent group of phases of the translated texts was selected.In the second subphase, the excerpts of both texts were analyzed individually for identification and classification of attitudinal values, the types of engagement and graduation resources. The second subphase also encompassed the calculation of the occurrence percentage of theAPPRAISAL categories in each excerpt. In the last subphase, the configurations of the appraising items identified in the translated texts and source texts were contrasted so that the semantic variations in the re-instantiation of attitude, engagement and graduation could be identified. Results show semantic variations between source texts and translated texts in the three domains of APPRAISAL. In attitude, there are variations in the coupling of the type, appraisal mode, loading and graduation of appraising items. Results also show semantic variations in the coupling and commitment of engagement. Two main tendencies of variation were identified: the translated texts are more explicit (particularly with the explicitation of lexical metaphors) and more heteroglossic than the source texts.